Safety and tolerability of controlled-release oxycodone on postoperative pain in patients submitted to the oncologic head and neck surgery - Cavalcanti,Ismar Lima (2014)
Objective: To evaluate the safety and tolerability of controlled-release oxycodone in the treatment of postoperative pain of head and neck oncologic resections.Methods: We conducted a prospective, observational and open study, with 83 patients with moderate to severe pain after head and neck oncological operations. All patients received general anesthesia with propofol, fentanyl and sevoflurane. Postoperatively, should they have moderate or severe pain, we began controlled-release oxycodone 20 mg 12/12 b.i.d on the first day and 10 mg b.i.d. on the second. We assessed the frequency and intensity of adverse effects, the intensity of postoperative pain by a verbal numeric scale and the use of rescue analgesia from 12 hours after administration of the drug and between 7 and 13 days after the last oxycodone dose.Results: The most common adverse events were nausea, vomiting, dizziness, pruritus, insomnia, constipation and urinary retention, most mild. No serious adverse events occurred. In less than 12 hours after the use of oxycodone, there was a significant decrease in the intensity of postoperative pain, which remained until the end of the study. The rescue medication was requested at a higher frequency when the opioid dose was reduced, or after its suspension.Conclusion: Controlled release oxycodone showed to be safe and well tolerated and caused a significant decrease in post-operative pain.